Unconventional Methods of Thermomechanical Treatment of Tool Steel - Aisman, David; Opatova, Katerina; Rubesova, Katerina; Jenicek, Stepan (Manufacturing Technology Journal, 2016)
Tool steels are traditional materials whose heat treatment routes are well-established. Despite that fact, unconventional treatment methods can be used, for instance for refining chromium carbides and general strengthening of the structure. One of the methods that considerably alter microstructure is semi-solid processing. By means of passing through the semi-solid state, the X210Cr12 steel (ČSN 19436) developed a microstructure of polyhedral austenite grains embedded in a carbide network. Forming of this material at an appropriate temperature led to recrystallization of the austenitic microstructure and to uniform distribution of carbides with a size of approximately 2 μm. By varying the rate of subsequent cooling, microstructures ranging from austenite to martensite could be obtained.
Keywords: semi-solid state; tool steel; dynamic recrystallization; metastable austenite